Study of Platform Workers’ Attitudes towards Social Security, Legal Regulation and Job Satisfaction: Age and Status Differences - Remeikiene, Rita; Gaspareniene, Ligita; Fedajev, Aleksandra; Hotkova, Aleksandra; Kovacs, Sandor (Transformations In Business & Economics, 2025)
The spread of digital labour platforms has sparked discussions about the future of work in the digital space. Improving working conditions for platform workers has become a central issue in recent research. This study aimed to examine how platform workers’ attitudes towards social security and job satisfaction vary by age and social status. Additionally, it reviewed previous research on platform working conditions and remuneration. The survey, conducted between 13 November 2023 and 20 May 2024, collected 437 responses on working conditions on digital platforms in Lithuania. The research methods included systematic and comparative literature analysis, as well as statistical data analysis using the Scheirer-Ray-Hare test and variance analysis. The results showed that attitudes towards platform work vary by age and social status. Platform workers aged 18-24 in Lithuania identified lower commuting, lunch, and rental costs as key advantages of platform work. Platform workers aged 34-55 were primarily concerned about the lack of paid breaks and holidays on digital platforms. Freelancers and students were concerned about irregular working hours, fluctuating workloads, and unpaid time spent searching for tasks. Parents prioritised flexibility and autonomy when working on platforms.